Influence of alkaline metal to phase transitions in ferroelastics M₂CdI₄ (M = K, Rb, Cs) - Yunakova, O.N.; Miloslavsky, V.K.; Kovalenko, E.N. (Functional Materials, 2005)
The absorption spectrum of thin films Cs₂Cdl₄ was studied in energy interval 3.6-5.1 eV and temperatures 90-410 К at their heating and cooling. The regularities are ascertained in behaviour of the thin films of isostructural compounds M₂Cdl₄ (M = К, Rb, Cs). With an increase of ion radius of alkali metal the temperatures of phase transitions are lowed, the value of temperature hysteresis in spectral position and halfwidth of exciton bands is decreased, and the temperature wash-out of phase transitions is increased. We supposed that these effects are connected with increase of squeezing of structural elements Cdl₄²⁻ in crystal lattices of compounds as a result of increase of alkali metal ion radius.